Explaining Emotional Labor’s Relationships with Emotional Exhaustion and Life Satisfaction: Moderating Role of Perceived Autonomy (2012)
This study assessed the extent to which two kinds of emotional labor (surface and deep acting) can lead to emotional exhaustion, reducing one’s overall life satisfaction. Based on Self-Determination theory, the importance of perceived autonomy was also studied in relation to how it moderates the relationship between emotional labor and emotional exhaustion. Data collected online from 241 staff employed at a university in central United States revealed that the relationship between surface acting and emotional exhaustion was stronger among people with lower perception of autonomy, which had an impact on overall life satisfaction. No significant relationship between deep acting and emotional exhaustion was found. Future directions should include studying the model on other samples and using a longitudinal design.